Factors Associated With High School Students’ Alcohol Consumption Across Three European Countries - Janáček, Julius (Journal of drug issues, 2021)
Based on a survey conducted in high schools in three countries—the Czech Republic, Italy, and Slovenia—this study investigates the factors influencing alcohol consumption among high school students. Our analysis is based on four linear regression models, with the dependent variable, Alcohol Consumption—one model for each country and a joint model for all countries. The results show that there are large differences as far as drinking habits and patterns across countries are concerned. Whereas the patterns of the Czech students are similar to those of Slovenian students, the behavior of the Italians shows more distinctive features. Factors positively related to alcohol consumption include cigarette smoking, marijuana consumption, time spent with friends (positive relations), sport activities, art engagement, and gender-female (negative relation). As factors regarding students’ psychological state are insignificant, it may be concluded that alcohol consumption among teenagers from our sample is a phenomenon that is insensitive to changes in character but sensitive to social environment and life circumstances. Our results can serve as a map showing various drinking patterns. Applicable results can be deduced.